The Effect Of Training And Work Motivation On The Performance Of Employees At PT. Proasia Broker Insurance And Consultants Of Bengkulu Branch - Indah Mardiana; Suswati Nasution; Rinto Noviantoro (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2023)
The important value of employee training is to develop the ability of employees to be more capable at work. It is also useful to increase their knowledge in other fields. Besides that, it is also useful for increasing work motivation in improving employee performance. The purpose of this study was to determine the effect of training and work motivation on the performance of employees at PT. Proasia Broker Insurance and Consultants of Bengkulu Branch, both partially and simultaneously. Data analysis method used were in the form of data quality tests (validity test, reliability test), multiple linear regression, coefficient of determination test (R2) and hypothesis testing (t test and f test) with the help of SPSS (statistical package for social science) version 25.0. The sample in this study totaled 37 respondents. The results of the study show that (a) training has a significant effect on the performance of employees at PT. Proasia Broker Insurance and Consultants Bengkulu Branch. Evidenced by a regression coefficient of 0.200, tcount > ttable (2.542 > 2.033) and a significant value of 0.016 ttable (3.161 > 2.032) and a significant value of 0.003 <0.05 Keywords: Training, Work Motivation, Employee Performance